Award-Winning Community Policing Strategies - Carlos Fields (My University, 2016)
The report highlights some of the winners of the International Association of Chiefs of Police Community Policing Award. Included are brief descriptions of innovative approaches, successfully developed and implemented at the local level, that aim to reduce crime and disorder.